Możliwości kształtowania zachowań prozdrowotnych wśród dzieci i młodzieży pokolenia „Digital Natives” - Leksy , Karina; Dworak , Alina (Studia Edukacyjne, 2020)
Regardless of how the contemporary young generation is described, there is no doubt that their permanent connection to the Internet and an incredible expertise in using information and communication technologies are one of the features that define those who grow up at the present time. Such strong involvement in digital media entails a number of health and development consequences for children and teenagers. In order to minimize the potential risks and negative effects of new media, it is essential to take action aimed at increasing awareness in terms of positive and negative aspects of using digital devices as well as at gaining abilities to use them in a way that is the most optimal and favourable for health. Currently, this issue constitutes a great challenge for teachers, parents, and carers for whom implementing health-seeking attitudes and behaviours of the young generation may be, taking into consideration the attractiveness of electronic media and virtual world, an enormously difficult task.